Validation of a multicellular tumor microenvironment system for modeling patient tumor biology and drug response - Roller, Devin G.; Hoang, Stephen A.; Rawls, Kristopher D.; Owen, Katherine A.; Simmers, Michael B.; Figler, Robert A.; Wulfkuhle, Julia D.; Petricoin, Emanuel F.; Wamhoff, Brian R.; Gioeli, Daniel (Scientific reports, 2021)
Lung cancer rates are rising globally and non-small cell lung cancer (NSCLC) has a five year survival rate of only 24%. Unfortunately, the development of drugs to treat cancer is severely hampered by the inefficiency of translating pre-clinical studies into clinical benefit. Thus, we sought to apply a tumor microenvironment system (TMES) to NSCLC. Using microvascular endothelial cells, lung cancer derived fibroblasts, and NSCLC tumor cells in the presence of in vivo tumor-derived hemodynamic flow and transport, we demonstrate that the TMES generates an in-vivo like biological state and predicts drug response to EGFR inhibitors. Transcriptomic and proteomic profiling indicate that the TMES recapitulates the in vivo and patient molecular biological state providing a mechanistic rationale for the predictive nature of the TMES. This work further validates the TMES for modeling patient tumor biology and drug response indicating utility of the TMES as a predictive tool for drug discovery and development and potential for use as a system for patient avatars.